2007
DOI: 10.1002/ijc.23001
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phenotypic characteristics of CD4+CD25highFoxp3+ Treg clones obtained from peripheral blood of patients with cancer

Abstract: CD25high T cells obtained from PBMC of normal controls (NC) or patients with squamous cell carcinoma of the head and neck (HNSCC) were plated at 1 cell/well in 96 well plates and expanded with anti-CD3/anti-CD28 Abs and 1,000 IU IL-2/ mL in the presence or absence of rapamycin (1 nM). All generated clones were evaluated for the phenotype by flow cyometry and suppressor function in CFSE-based proliferation assays. Clones had heterogeneous CD25 expression levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…These results are not novel because we have previously demonstrated that rapamycin selectively blocks the in vitro expansion of human CD4 + CD25 − conventional T cells, while allowing nTreg growth [3,5]. In addition, the finding that rapamycin-expanded nTreg retain a broad T cell receptor (TCR) repertoire shown by Guillot-Delost et al [1] was also reported in our previous publications [5,8]. Finally, the authors state that 'Although several strategies that combined stimulation of TCR, CD28 and IL-2R have been developed for long-term culture and polyclonal expansion of nTreg in recent years [9][10][11], none of them were efficient enough to generate large numbers of nTreg'.…”
supporting
confidence: 66%
“…These results are not novel because we have previously demonstrated that rapamycin selectively blocks the in vitro expansion of human CD4 + CD25 − conventional T cells, while allowing nTreg growth [3,5]. In addition, the finding that rapamycin-expanded nTreg retain a broad T cell receptor (TCR) repertoire shown by Guillot-Delost et al [1] was also reported in our previous publications [5,8]. Finally, the authors state that 'Although several strategies that combined stimulation of TCR, CD28 and IL-2R have been developed for long-term culture and polyclonal expansion of nTreg in recent years [9][10][11], none of them were efficient enough to generate large numbers of nTreg'.…”
supporting
confidence: 66%
“…Nor can we ignore the role of the suppressive effects of tumor cells on the functions of immune cells. This can lead to the phenomenon of anergy and immunological tolerance in cancer patients, and it points to the importance of regulatory CD4 + lymphocytes, demonstrating an immunosuppressive effect on effector cells [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + cells which, by the immunosuppressive activity directed against the effector cells, also contribute to the inhibition of antitumor immune mechanisms and increasing cancer progression [2,6,8,[15][16][17][18][19][20][21][22][23]. The causes of the dysfunction of T lymphocytes, both CD4 + and CD8 + cells and absence of stimulation of cells participative in the cellular immune response to tumor antigens, also include changes in the level of secreted cytokines, marked in the peripheral blood in patients with laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%